Physicochemical Properties and Morphological Characteristics of Composite Flour Added with Cornlettes (Zea Mays) for Functional Food Ingredient - Wan Rosli, W. I.; Nurul Aliim, Z. A. (American-Eurasian Network for Scientific Information (AENSI Publisher), 2016)
Cornlettes (young corn) is rarely used in maximizing its usage as well as to accommodate the demands in functional food development. Objective: This study aimed to investigate physicochemical properties and morphological characteristics of composite flour containing cornlettes powder (CP) which partially replacing wheat flour. Composite flour was prepared by using CP mixed with wheat flour (WF) with the proportion of 10:90, 20:80, 30:70 and 100:0 (CP: WF). Results: Amylose contents significantly increased when the percentage of cornlettes powder in composite flours is increased. The highest amylose content was found in 100% CP sample (4.40g/20g) while the lowest amylose content was found in control sample (0.072g/20g). The percentage of swelling power in composite flour added with CP was significantly higher than control and there is significant difference in the setback viscosity of the composite flour starch samples. Composite flour shows uniformed wheat starch granules which clustered with irregular shape of cornlettes starch granule. Conclusion: Addition of CP to partially replace wheat flour to form composite flour has resulted in improvement of swelling power and amylose composition while slightly altering the starches morphological structures. Composite flour with higher proportions of CP (30:70) can be used to partially replace wheat flour in order to meet the demands of food production.